O impacto dos acordos do tipo sul-sul e norte-sul sobre o comércio dos países em desenvolvimento - Lima, Bianca Guaracy Carvalho da Cruz (2017)
This study aims to value what type of agreement promotes higher impact on the developing countries trade, the South-South or the North-South agreements, considering their levels of integration and the regulation in which they are submitted. Therefore, gravity equations were used to estimate the trade creation and trade diversion coefficients of South-South and NorthSouth agreements, inserting fixed effects to control for multilateral resistance terms and unobserved heterogeneity. The results demonstrate that when only the multilateral resistance terms are controlled, the South-South agreements with higher level of integration and notified under the GATT Art. XXIV provide the highest impact on the trade growth, but when the country-pair fixed effects are included, the agreements with a great number of countries show similar results, regardless their level of integration and the development degree of theirs’s member countries. Therefore, in general, the South-South agreements provide higher impact than the North-South kind only when both have a small number of member countries.